Deconstruction in Qohelet: A Response to Mark Sneed - Ortlund, Eric Nels (Journal for the study of the Old Testament, 2015)
Ecclesiastes has received a number of postmodern-styled readings in recent decades. One such piece by Mark Sneed distinguishes itself by applying deconstructive methods to show Qohelet's internal contradictions. Although Sneed's argument is helpful and illuminating, certain aspects of Derrida's articulation of ‘deconstruction’ are not well represented. In this article, an alternative ‘deconstruction’ of Qohelet is offered which attempts to witness to tensions within the text instead of applying predetermined concepts from outside.